Satisfação dos consumidores com os serviços públicos: uma análise dos impactos de políticas públicas no setor elétrico brasileiro - Verdolin-Benedito, Patricia (Universidade Federal de São Carlos, 2024)
Since 2000, the perception of the satisfaction of electricity consumers has been collected and published by the Iasc – Aneel Consumer Satisfaction Index. Aneel, through resolutions, has promoted the customer-focused mentality among distributors and, in addition to encouraging awards, has made ISO9001 certification compulsory in processes directly related to customers. The objective of this study was to survey the policies, guidelines and strategic actions in the Brazilian electricity sector and how they contributed to the establishment of metrics to evaluate the performance of the sector, as well as to understand the impact of government action on the results of the indicators. For this, the data available from the Iasc – Aneel Consumer Satisfaction Index were used, which were submitted to statistical analysis to evaluate its performance. Given the statistical analysis, it was possible to assume as true the initial hypothesis that the implementation of ISO9001 contributed to improving the perception of the quality of services provided.
Consumer satisfaction with public services: an analysis of the impacts of public policies on the brazilian electricity sector
Keywords: Satisfação do cliente; ISO9001; Distribuição de energia elétrica; Regulação; Qualidade de serviço; Satisfaction; Energy distribution; Regulation; Quality; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO